2016 IEEE Congress on Evolutionary Computation (CEC) 2016
DOI: 10.1109/cec.2016.7743811
|View full text |Cite
|
Sign up to set email alerts
|

Multi objective optimization of a fuzzy logic controller for energy management in microgrids

Abstract: This paper presents a novel power flow optimization strategy in Micro Grids (MGs) connected to the main grid. When the MG includes stochastic energy sources, such as photovoltaic and micro eolic-generators, it is very useful to rely on Energy Storage Systems (ESSs) to buffer energy. In fact, an ESS can be employed to perform several functionalities, related to different user requirements, such as power stability, peak shaving, optimal energy trading, etc. The Energy Management System is based on a Fuzzy Logic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…As there is no need of the FC, on the grounds that, all the power request is fulfilled with wind/PV, so its output power is zero all through this interim amid hours 7–20. Table 12 demonstrates comparison results of various optimisation algorithms: evolutionary programming (EP) [53], SOGA [54], SOPSO [41], enhanced bee colony optimisation (EBCO) [43], MOGA [55], and the proposed MOPSO algorithm during different operating modes. It can be observed that the proposed MOPSO optimisation strategy gives the optimum performance in terms of obtained optimum solutions for the problem, the minimum number of iterations required to reach to the optimum solutions.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As there is no need of the FC, on the grounds that, all the power request is fulfilled with wind/PV, so its output power is zero all through this interim amid hours 7–20. Table 12 demonstrates comparison results of various optimisation algorithms: evolutionary programming (EP) [53], SOGA [54], SOPSO [41], enhanced bee colony optimisation (EBCO) [43], MOGA [55], and the proposed MOPSO algorithm during different operating modes. It can be observed that the proposed MOPSO optimisation strategy gives the optimum performance in terms of obtained optimum solutions for the problem, the minimum number of iterations required to reach to the optimum solutions.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A multi-objective system using an FLC for energy management, as proposed in [37] and extended in [38] and in [39], is a real-time charging strategy, with the rule weights and Membership Function (MF) parameters being the search space of the optimization algorithm.…”
Section: Optimal Charging Strategy Of Essmentioning
confidence: 99%
“…Based on [38], there are two possible objectives for the charging strategy: (i) the financial objective function, purely based on the cost of buying/selling energy in different times; and (ii) the battery stress level, to represent the physical degradation of the battery.…”
Section: Optimal Charging Strategy Of Essmentioning
confidence: 99%
“…This proposed technique improves the microgrid profits without affecting the BESS. The Energy Management System of this paper [19] includes a Fuzzy Logic Controller (FLC) which uses Multi-Objective Genetic Algorithm for optimization. It improves the net profit of the generating units and state of health of batteries.…”
Section: Fig2par Curvementioning
confidence: 99%